2021
DOI: 10.37729/scripta.v8i1.799
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Reading Narrative Text Using Story Face in Vocational High School

Abstract: The aims of this research are to describe the students‘ reading achievement and to find out the effectiveness of using story face in teaching reading narrative text. This research is quantitative using quasi-experimental design with purposive sampling technique.  The population was tenth grade students and the sample was the students of X TKR 2 consist of 37 students as experimental group and X TKR 13 consist of 33 students as control group. The technique of collecting data are making instrument, expert judgme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Developing one's vocabulary is an essential part of learning a second language, according to students, teachers, textbook authors, and academics alike (Schmitt, 2008). In order for students to succeed in school, they must master four key skills: listening, speaking, writing, and reading (Syafitri et al, 2021)). Many pupils lack the vocabulary necessary to communicate clearly, comprehend what they read, or write well in English because they don't know what language to use.…”
Section: Resultsmentioning
confidence: 99%
“…Developing one's vocabulary is an essential part of learning a second language, according to students, teachers, textbook authors, and academics alike (Schmitt, 2008). In order for students to succeed in school, they must master four key skills: listening, speaking, writing, and reading (Syafitri et al, 2021)). Many pupils lack the vocabulary necessary to communicate clearly, comprehend what they read, or write well in English because they don't know what language to use.…”
Section: Resultsmentioning
confidence: 99%
“…An earlier study by Sidik et al (2018) indicated that employee performance was not influenced by the work environment's influence on employee behavior. The working environment encompasses not only the interpersonal connections between coworkers and supervisors, but also the physical surroundings in which employees do their duties (Syafitri et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Narrative paragraph is a paragraph that tells a story, whether fictional or non-fictional, written in chronological order by using time order signal which contains orientation, complication, resolution, and re-orientation (Wirastuti & Mantra, 2019). Narrative text tells stories or past events and entertain or amuse which consisted of three generic structures namely; orientation, complication, and resolution (Syafitri et al, 2021). Writing consists of fives aspects namely; content, organization, vocabulary, language use, and mechanics.…”
Section: Introductionmentioning
confidence: 99%